Asuhan Keperawatan Pada Pasien Post Kolesistektomi Dengan Nyeri Akut di Rumah Sakit Wilayah Depok - Lekatompessy, Roland; Andriani, Sindy; Saudi, La (Politeknik Karya Husada, 2022)
Cholelithiasis also known as gallstones is a disease in which stones are found in the bile or gallbladder, or both. Cholelithiasis is typically caused by bile components such as cholesterol, bilirubin, and calcium accumulating in the gallbladder. This study aims to understanding and providing nursing care to post cholecystectomy patients in Depok Regional Hospital's. To understand nursing problems in post cholecystectomy patients, a descriptive analytic approach in the form of case studies was used. Data was gathered through interviews, observations, physical examinations, and documentation reviews. A medical-surgical nursing care format was used for data collection. Mrs. R and Mr. K with a medical diagnosis of cholelithiasis, the results of the following nursing diagnoses were obtained; for acute pain problems, the results showed that the pain scale decreased to two from a range of ten, and the patient did not wince in pain. Mrs. R and Mr. K second diagnosis, physical mobility, revealed that the patient was able to do activities even if they had to be done slowly. Meanwhile, Mrs. R third diagnosis is nausea, and the results are decreased nausea and increased appetite. Mr. K third diagnosis, a sleep pattern disorder, has resulted in the patient still having difficulty sleeping. Most of the nursing diagnoses in the two patients were resolved within 3x24 hours of treatment, only the diagnosis of sleep pattern disorders was resolved in part because the patient still had difficulty sleeping.